2014
DOI: 10.1007/s10753-014-9968-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IL-8 Nasal Lavage Levels and the Effects of Nasal Involvement on Disease Severity in Patients with Stable Chronic Obstructive Pulmonary Disease

Abstract: Interleukin 8 (IL-8) is used to evaluate the severity of inflammation in the airways. The aim of this study was to evaluate patients with chronic obstructive pulmonary disease (COPD) for the presence of upper respiratory tract involvement by questioning patients regarding nasal symptoms and by measuring levels of IL-8 in nasal lavage material. A total of 47 COPD patients and 23 healthy controls were enrolled in this study. Pulmonary function tests were performed for all participants who were asked to complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In the 50 FORTE study participants discussed above, IL-2 was higher in COPD patients, but was lower in rapid decliners compared to stable COPD patients [ 44 ]. Similarly, in small studies IL-8 has been reported to be elevated in COPD patients in smaller studies with less than 100 subjects [ 57 , 58 ]. This is the first large study to show that IL-8 is independently associated with progression of emphysema by CT scan and additional studies in independent longitudinal COPD cohorts should consider measuring IL-8.…”
Section: Discussionmentioning
confidence: 98%
“…In the 50 FORTE study participants discussed above, IL-2 was higher in COPD patients, but was lower in rapid decliners compared to stable COPD patients [ 44 ]. Similarly, in small studies IL-8 has been reported to be elevated in COPD patients in smaller studies with less than 100 subjects [ 57 , 58 ]. This is the first large study to show that IL-8 is independently associated with progression of emphysema by CT scan and additional studies in independent longitudinal COPD cohorts should consider measuring IL-8.…”
Section: Discussionmentioning
confidence: 98%
“…IL-8 is a major chemoattractant to neutrophils, which are responsible for inducing and sustaining the inflammatory state [ 16 ]. A close correlation between the number of neutrophils in induced sputum in COPD patients, the IL-8 level, and clinical outcome of the illness has been reported [ 17 ]. On the contrary, neutralization of IL-8 by a monoclonal antibody recognizing IL-8 in COPD causes a decrease of exacerbation frequency and clinical symptoms [ 18 ].…”
Section: Introductionmentioning
confidence: 92%
“…Both IL-1β and IL-6 mediate inflammation by binding to their respective receptors on endothelial cells to induce the expression of leukocyte adhesion molecules such as ICAM-1. ICAM-1 interacts with counter receptors on the surface of leukocytes to mediate the migration of leukocytes, and it is also involved in the arrest of leukocytes on inflamed endothelium (Lesniak et al 2013 ; Winter et al 2002 ; Celic et al 2015 ). The macrophage inhibitory protein 1a (MIP1a) takes part in the leukocyte chemotaxis and correlates with IL-8 (Gamucci et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%